A study on mean platelet volume in ischemic cerebrovascular stroke - Patel, Vitan; Parmar, Mahendra; Shah, Kinjal; Joshi, Rishikesh (International Journal of Advances in Medicine, 2018)
Background: Ischemic Cerebrovascular stroke is one of the largest cause of death and disability. It is usually caused by thrombosis or thromboembolic phenomena. Large platelets are more reactive, produce more prothrombotic factors and aggregate more easily, and can be a major risk factor/indicator for stroke. While the Mean Platelet Volume (MPV) has been studied in detail in cases of IHD, very few studies have been done in stroke, and none in India – prompting this study. We aim to determine whether an association exists between MPV and incidence/severity of stroke. Methods: The study was carried out among fifty patients with an acute ischemic stroke. Clinical severity was assessed using Modified Rankin‘s scale. MPV was measured using an automated analyzer. Fifty controls were recruited and analysed. Results: MPV has got a statistically significant correlation with Ischemic stroke with a p value of < 0.0001. Average MPV in cases was 9.78+1.25 fl vs. controls who average 8.30+1.14 fl. We did not find a statistically significant correlation between clinical severity of stroke and MPV (P = 0.550). Conclusions: This study has shown an elevation of MPV in acute phase of Ischemic stroke. Within this relationship and adjusting for other significant variables in multivariate regression analysis, it can be stated that an increase in MPV is independently associated with stroke. Further research is required into the role of platelet volume in stroke pathology, outcome, and, most importantly, in individuals at risk for stroke.